1980
DOI: 10.1530/acta.0.0950505
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of insulin-like growth factor (IGF) and its carrier protein in various metabolic disorders

Abstract: Abstract. The levels of insulin-like growth factors (IGF), two somatomedin-like polypeptides of human serum and of their carrier protein were determined in sera of patients with various metabolic disorders. IGF was measured by 4 different methods (fat pad and fat cell assay and competitive protein binding assay measuring total IGF, and a radioimmunoassay for IGF I) after extraction by acidic gel filtration on Sephadex G-50. This procedure is necessary to separate IGF from the carrier protein, which interferes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 21 publications
6
66
0
Order By: Relevance
“…In accordancew ith previous studies (15)(16)(17)(18), we confirmed that fasting serum concentrationso ft otal andf reeI GF-I were reduced and IGFBP-1 levels elevated,w hile IGF-I:IGFBP-1b inaryc omplex and IGFBP-2 tended to be higher in cirrhotic patients, as compared with healthycontrols. In addition,weshowed that thec irculatingb ioactivityo fI GF-I wasa lso subnormal in cirrhosis, and that levels, in contrast to totala nd free IGF-I, declined during the OGTT.T his observation mayb ee xplained by the higher levels of unsaturatedI GFBP-1 (i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordancew ith previous studies (15)(16)(17)(18), we confirmed that fasting serum concentrationso ft otal andf reeI GF-I were reduced and IGFBP-1 levels elevated,w hile IGF-I:IGFBP-1b inaryc omplex and IGFBP-2 tended to be higher in cirrhotic patients, as compared with healthycontrols. In addition,weshowed that thec irculatingb ioactivityo fI GF-I wasa lso subnormal in cirrhosis, and that levels, in contrast to totala nd free IGF-I, declined during the OGTT.T his observation mayb ee xplained by the higher levels of unsaturatedI GFBP-1 (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, in comparison to healthysubjects, increasedcirculating levels of IGFBP-1, but lower total and free IGF-I, are characteristic features of liver cirrhosis (15)(16)(17)(18)(19). Furthermore, one of the major health problems in cirrhotic patients is malnutrition, whichexertsaserious adverse effect on clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in IGFBP concentrations contribute to the limitations known for a variety of IGF1 assays (32). To circumvent these problems, we used a classical and time-consuming assay in which carrier proteins are removed before the samples are incubated with the antibodies (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in somatomedins measured by a variety of methods have been observed in studies on adults with chronic liver disease. Wu et al (6) initially demonstrated depressed somatomedins (measured as sulfation factor) in adults with cirrhosis, and this finding was confirmed in additional studies using radioreceptor assays (7) and RIA (8,9). Unfortunately, the role of malnutrition in these patients was not considered.…”
mentioning
confidence: 97%